The King that Devours his People: Conceptual Notes on a Sculpture Project - Akabuike , Chikelue Chris (South Asian Journal of Social Sciences and Humanities, 2020)
This paper discusses the implications of personality cult leadership style in the Nigerian context. It sought to situate the work under discussion in a way that it contributes to the ongoing dialogues and debates, within the works of literary and visual artists who have sought to speak against personality cult phenomena. It uses the author’s sculptural woodwork titled, The King that Devours His People, a process oriented studio exploration, produced as a visual metaphor using the joinery technique as a method. Thus, the instrumentalist essences of the studio project’s formal features are discussed in ways that draw out the implications of personality cult leadership style, especially, in the Nigerian setting. The generated visual imageries articulate the socio-political activities of leaders and its’ consequences on the led. It meteorologically addresses the man inhumanity to man perpetrated by the Nigerian leaders on the masses. It particularly focuses on mobilizing against personality cult syndrome. The project significantly rationalizes the history of Nigeria and her people who have been shaped by one form of leadership or another. Thus, the unique joinery method, that gave rise to the formal features shows how artistic media and processes is used as a metaphor to discuss the implications of personality cults as a way of interrogating the strength and limitations of the effect of personality cults within the Nigerian situation.